Digital Marketing Developing Online Business for Students of SMKN 48 Jakarta - Sibarani, Bintang B; Juhaeti, Juhaeti; Afrianda, Rio; Hermawan, I Gusti Ngurah Willy; Permatasari, Rita Intan; Wijayanti, Dian; Salim, Firna Julia; Fallah, Raka Arbian; Ardini, Siska (Jurnal Pengabdian Masyarakat Bhinneka, 2025)
The rapid development of information and communication technology has significantly transformed marketing strategies from conventional methods to digital marketing. This transformation offers great opportunities for entrepreneurs, including vocational high school students, to develop online businesses. SMKN 48 Jakarta, particularly in the Online Business and Marketing department, has strong potential in this field; however, many students still lack adequate knowledge and skills in effectively applying digital marketing strategies. This Community Service Program (PKM) aims to provide training and mentoring for 67 students of SMKN 48 Jakarta through participatory and educational methods, including literacy-based socialization, hands-on training, interactive discussions, and learning outcome evaluations. The training materials cover fundamental concepts of digital marketing, the use of social media, creative content creation, and online store management. The results indicate an improvement in students’ understanding and skills in utilizing digital platforms for business development, as well as increased entrepreneurial motivation. This program is expected to make a tangible contribution to producing young entrepreneurs who are creative, competitive, and adaptive to technological advancements.